2007
DOI: 10.1016/j.virol.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of viral replication reduces regulatory T cells and enhances the antiviral immune response in chronic hepatitis B

Abstract: Regulatory T cells (Treg) play a key role in the impaired immune response that is typical for a chronic Hepatitis B virus (HBV) infection. To gain more insight in the mechanism that is responsible for this impaired immune response, the effect of viral load reduction resulting from treatment with the nucleotide analogue adefovir dipivoxil on the percentages of Treg and HBV-specific T-cell responses was analyzed. Peripheral blood mononuclear cells (PBMC) of 12 patients were collected at baseline and during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 27 publications
10
73
2
Order By: Relevance
“…In this study, the results demonstrated a negative correlation between HBV-DNA levels and HBV-specific CTL responses in untreated CHB patients. These findings are in agreement with previous studies (14,17) and strengthen the evidence for an independent effect of viral load on the cellular immune response. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the results demonstrated a negative correlation between HBV-DNA levels and HBV-specific CTL responses in untreated CHB patients. These findings are in agreement with previous studies (14,17) and strengthen the evidence for an independent effect of viral load on the cellular immune response. …”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrate a positive correlation between the magnitude of the HBV-specific T-cell responses and the duration of the HBV DNA suppression. The independent effect of the length of HBV DNA suppression on specific immune response, found in this study, was partly in accordance with previous studies (16,17). It is widely hypothesized that the T-cell function exhaustion of CHB patients occurs because of the prolonged exposure of T cells to high quantities of viral antigens and that T-cell resting from antigenic stimulation is a crucial requirement for restoration of a functional antiviral T-cell response (3,5,9,18).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, inhibition of viral replication reduces Treg counts and enhances the antiviral immune response in chronic hepatitis B patients (38). Tregs may also limit liver injury by controlling inflammation.…”
Section: Cd25mentioning
confidence: 99%
“…It has been reported that elevated numbers of Tregs can inhibit HBV-specific immune responses in a dose-dependent manner. 8 Depletion of Tregs has been shown to increase IFN-c production by HBV Ag-stimulated peripheral blood mononuclear cells. 20 Therefore, it is likely that the HBV-mediated enhancement in Tregs may, at least in part, contribute to immune tolerance and persistent infection in CHB patients.…”
Section: Enhancing Immune Response By Etv and Advmentioning
confidence: 99%
“…4 Recent findings suggest that regulatory T cells (Tregs) may also play a role in regulating immune responses to HBV infection. 8 High levels of Tregs have been detected in CHB and are thought to be responsible for the chronicity of hepatitis B infection, probably by inhibiting HBV-specific T-cell responses. However, Treg function also may be beneficial, limiting immune-mediated liver damage.…”
Section: Introductionmentioning
confidence: 99%